1996
DOI: 10.1021/la960169j
|View full text |Cite
|
Sign up to set email alerts
|

Surface Chemical Characterization Using XPS and ToF-SIMS of Latex Particles Prepared by the Emulsion Copolymerization of Methacrylic Acid and Styrene

Abstract: A series of colloids based on poly(styrene) were prepared by emulsion copolymerization with various proportions of methacrylic acid. X-ray photoelectron spectroscopy (XPS) and time-of-flight secondary ion mass spectrometry (ToF-SIMS) were used to monitor changes in particle surface composition and indicated a substantial enrichment of the methacrylic acid component. Further evidence for the presence of carboxyl groups at the particle surfaces was provided by electrophoretic mobility measurements, which showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 53 publications
2
24
0
Order By: Relevance
“…The presence of PSS À in the PAni nanofiber material was confirmed from the appearance of a shake-up satellite peak (291.6 eV) in the C 1s region spectrum ( Figure S10 in the Supporting Information), characteristic of p!p* transitions of localised conjugated systems, consistent with the aromatic arene rings of the PSS À . [62,81,82] This was further supported by the S 2p region of the spectra, which showed a peak at 168.5 eV (corresponding to the S 2p 3/2 component of the doublet, Figure S11 in the Supporting Information), in agreement with previous literature values for PSS À . [83][84][85] Significantly, TEM analysis of these samples showed that the ES-PAni-coated nanofibers were still intact and had retained the lengths and narrow length distributions of the original PFS 25 -b-P2VP 425 micellar templates ( Figure S7 in the Supporting Information).…”
Section: T [8c]supporting
confidence: 90%
“…The presence of PSS À in the PAni nanofiber material was confirmed from the appearance of a shake-up satellite peak (291.6 eV) in the C 1s region spectrum ( Figure S10 in the Supporting Information), characteristic of p!p* transitions of localised conjugated systems, consistent with the aromatic arene rings of the PSS À . [62,81,82] This was further supported by the S 2p region of the spectra, which showed a peak at 168.5 eV (corresponding to the S 2p 3/2 component of the doublet, Figure S11 in the Supporting Information), in agreement with previous literature values for PSS À . [83][84][85] Significantly, TEM analysis of these samples showed that the ES-PAni-coated nanofibers were still intact and had retained the lengths and narrow length distributions of the original PFS 25 -b-P2VP 425 micellar templates ( Figure S7 in the Supporting Information).…”
Section: T [8c]supporting
confidence: 90%
“…This peak corresponds to the MA monomer unit minus a hydrogen (C 4 H 5 O 2 − ) and is observed in the negative ion spectra of all methacrylate polymers (3436). As shown in Figure 6 the intensity of this peak is highest for the two grafted MA/NaSS films and nearly zero for the two grafted NaSS films.…”
Section: Resultsmentioning
confidence: 92%
“…The PS latex was prepared by emulsifier‐free emulsion polymerization of St with surfmer [methacrylic acid (MAA)] according to the procedure as reported previously 36. St (10 mL) and 2 mL MAA were added to 95 mL distilled water in a three‐necked round bottom flask fitted with a condenser and a magnetic stirrer and purged with nitrogen.…”
Section: Methodsmentioning
confidence: 99%